Dynamics of non-structural carbohydrates in Pinus pallasiana D. Don needles under different forest growth conditions of ravine anti-erosion plantations - Bessonova, Valentina; Бессонова, Валентина Петрівна; Yakovlieva-Nosar, Svitlana; Яковлева-Носарь, Світлана Олегівна (Polska Akademia Nauk, 2022)
The research was aimed at analysing the peculiarities of non-structural carbohydrate metabolism in the needles of Pinus pallasiana D. Don in anti-erosion plantations on the slope and in the thalweg of the Viyskovyi ravine under different forest growth conditions. The ravine is located in the Dnipropetrovsk region and belongs to the southern geographical variant of ravine forests. The studied plants grew at three experimental sites of man-made plantation: in the thalweg (forest growth conditions – mesophilic, fresh, CL2), in the middle part of the slope of the southern exposure (mesoxerophilic, somewhat dry, or semi-arid, CL1) and on the upper part of this slope (xerophilic, arid, CL0–1). Changes in glucose, fructose, reducing sugars, sucrose and starch during the period from May to October were studied. The concentration of osmotically active substances (glucose, sucrose) increases in the months with the most unfavourable hydrothermal parameters, especially in plants of mesoxerophilic and xerophilic forest growth conditions. The dynamics of fructose content revealed two maxima (July and October), when the concentration of glucose tends to increase steadily, with the highest values found in October. During the study period, the level of fructose in the needles under the arid conditions of the upper and middle parts of the slope was much lower than under the fresh conditions of the thalweg. The dynamics curve of the starch content tends to decrease from the maximum values in May to the first minimum in August. It is followed by some increase in the concentration of this polysaccharide that does not reach the previous values. The second minimum is registered in October. Such changes in the level of starch in the needles of plants are observed under all forest growth conditions. The decrease in polysaccharide content is consistent with the increase in glucose and sucrose, especially in August. A more significant increase in the concentration of soluble osmoprotective sugars (glucose, sucrose) in P. pallasiana needles under unfavourable hydrothermal conditions compared to normal moisture conditions indicates the ability of plants to adapt to mesoxerophilic and xerophilic conditions. Дослідження було спрямовано на аналіз особливостей неструктурного вуглеводного обміну в хвої Pinus pallasiana D. Don в протиерозійних насадженнях на схилі та в тальвезі Війського яру за різних умов росту лісу. Яр розташований у Дніпропетровській області і відноситься до південних географічний варіант ярових лісів. Досліджені рослини росли на трьох дослідних ділянках штучних насаджень: у тальвезі (умови росту лісу – мезофільні, свіжі, CL2), у середній частині схилу південного оголення (мезоксерофільна, дещо суха або напівпосушлива, CL1) і на верхній частині цього схилу (ксерофільна, посушлива, CL0–1). Зміни вмісту глюкози, фруктози, редукційних цукрів, сахарози та крохмалю були вивчені в період з травня по жовтень.
Динаміка неструктурних вуглеводів в хвої Pinus pallasiana Д. за різних умов росту лісу ярівних протиерозійних насаджень
Keywords: ravine; яр; man-made plantation; штучні насадження; Crimean pine; сосна кримська; forest growth conditions; умови росту лісу; sugars; цукри; starch; крохмаль